Diabetes melitus tipe 2 dan perilaku dokter keluarga di Kota Manado - Raranta, Deylafaith Graniella; Kuhon, Frelly Valentino; Palandeng, Henry Malcom Frank (Jurnal Kedokteran Komunitas dan Tropik, 2023)
Background: Diabetes Mellitus (DM) is one of the non-communicable diseases included in the top 10 causes of death worldwide, with 6.7 million reported cases. The prevalence of DM in North Sulawesi Province ranks 4th, with a prevalence of 2.3%, exceeding the national average. Comprehensive treatment, which does not solely focus on the patient's disease aspect, is needed to address the increasing cases of DM. The Indonesian government, through the Social Health Insurance Administration Body (BPJS), operates a primary care system that utilizes family physicians as the frontline in serving the community. However, several conducted studies reveal a lack of frequency in the knowledge, attitude, and practice of family physicians towards DM management.Aim: To determine the behaviour (knowledge, attitude, and action) of family physicians management of type 2 DM in Manado City.Methods: This study is a descriptive study with a cross-sectional research design.Results: The level of knowledge, attitude, and practice of family physicians in type 2 DM management was categorized as good at 98.2% and sufficient at 1.8%.Conclusion: The behaviour of family physicians in Type 2 DM management in Manado City is considered good.Keywords: behaviour, type 2 diabetes mellitus, family physicians